Investigation of Student Attitudes and Understanding in General Chemistry - Zidon, Hannah (My University, 2015)
This project aims to analyze the state of the current Chemistry 103 lab manual in order to understand the demands place on entry-level chemistry students.
Color poster with text.
Keywords: Levels of inquiry; Chemistry students; Chemistry; Posters